Image In The Artistic Expression Of The Spirit Of Children - Nabiyeva Zarina Nabiyevna (Research Parks Publishing LLC, 2021)
The article deals with the expression of the image of children in fiction and its figurative interpretations, including Antoine de Saint-Exupery the story of the